Mode of Action of Primaquine: Preferential Inhibition of Protein Biosynthesis in Bacillus megaterium - Olenick, John G. (1972)
The growth of a strain of Bacillus megaterium was prevented by a minimal inhibitory concentration of primaquine of 52 μg/ml or 2 × 10(−4)m. When exponentially growing cultures received the drug at 6 × 10(−4)m, the rate of growth was drastically reduced and no further growth occurred after 15 min of exposure. At this concentration, primaquine was bactericidal, causing a 50% reduction in the viable population after one doubling time of 45 min. Supplying primaquine to cultures 30 min after adding radioactive-labeled phenylalanine, thymidine, uracil, or diaminopimelic acid produced an immediate and complete inhibition of protein biosynthesis but no inhibition of deoxyribonucleic acid biosynthesis for at least 15 min, and caused the formation of ribonucleic acid and cell wall polymer to proceed linearly at rates similar to those established prior to the addition of drug. This pattern of inhibition of macromolecular biosyntheses suggests that the major in vivo action of primaquine in B. megaterium is to block protein synthesis.